Modelagem numérica do comportamento mecânico de soldas ponto por fricção - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Friction Spot Welding (FSpW) is a technique that uses mechanical and thermal energy generated by a rotating tool, creating joints by a spot weld. This technique was initially designed to joining light alloys that are difficult to weld by conventional methods (such as resistance electric welding, for example). Virtually any material with a certain amount of plasticity can be welded by this technique. Besides allowing the union of materials that can not be welded by conventional methods, the FSpW generates almost no waste, does not emit pollutant gases and, because there is no inclusion of other material for marriage, facilitates recycling. Being a relatively new process (patented in 2005), it is necessary to study it in order to know the parameters that result in the best features, allowing reproducibility of the joints and greater reliability. Thus, the study of the mechanical behavior of the joint is of great value as it is an important aspect to be considered in the choice of welding processes to be used in projects in engineering. The objective of this work was study approaches for simulating the mechanical behavior of welds FSpW in shear request. Initially, it made an extensive literature review on the process in order to gain knowledge about the mechanical behavior of FSpW joins. Was used the ANSYS WORKBENCH software for creating two models, one model covering the elastic-plastic joint regime, and a model based on simulation of the interface delamination between the plates. The implementation of the models was performed using experimental datas from FSpW specimens, as the hardness profile and force-displacement curves obtained from shear test. Different approaches of material were tested and the numerical results were compared with the experimental curve. It was the model contact condition as the main feature for setting the numerical behavior so as to reproduce the real behavior.
Keywords: Mechanical Engineering; Friction Spot Welding; Numerical modeling; CNPQ::ENGENHARIAS; Engenharia mecânica; Soldagem por fricção; Modelagem numérica